Survey of nutrition knowledge of Kuwaiti health influencers in social media - Allafi, Ahmad R (Acta Biomedica Atenei Parmensis, 2020)
Objective: The aim of this study was to determine whether nutrition knowledge differs between male and female Kuwaiti health influencers in social media (Instagram).Design: A cross-sectional study was conducted to determine the nutrition knowledge of male and female Kuwaiti health influencers in social media (Instagram) utilizing a multiple-choice questionnaire with sixteen questions.Setting: Kuwaiti health influencers in social media (Instagram).Subjects: One hundred Kuwaiti health influencers (fifty males; fifty females) in social media (Instagram).Results: A response rate of 70% was accomplished (thirty-two males; thirty-eight females). The correctly answered questions had a mean percentage of 60% with averages of 65% and 60% for correct responses by males and females, respectively (P=0.039). Only, two questions demonstrated significantly different scores for male and female groups (P